The rise of fintech: Bibliometric analysis of global growth, emerging themes and the quality of scientific contributions - Zakaria, ENNOUHI; Abdelhalim, LAKRARSI (International Journal of Innovative Research and Scientific Studies, 2025)
This study conducts a comprehensive bibliometric analysis of fintech adoption research from 2016 to 2024, identifying key trends, influential contributors, and emerging themes. To achieve this goal, we leverage data from Scopus and the SCImago Journal Rank to analyze the evolution of fintech scholarship, focusing on publication growth, geographic distribution, and scientific impact through the H-index and journal quartile rankings. In addition, advanced visualization tools, such as VOSviewer, are utilized to map keyword co-occurrences, collaboration networks, and citation dynamics. Our findings reveal that fintech-related research has experienced a substantial surge, particularly since 2020, primarily due to accelerated digital transformation and the COVID-19 pandemic. Moreover, Asia and Europe have emerged as leading contributors to both research output and innovation. Specifically, the dominant thematic clusters include blockchain, artificial intelligence, financial inclusion, and regulatory challenges. However, critical issues such as cybersecurity, trust, and regulatory uncertainty persist, which underscores the need for further investigation. From a practical perspective, these insights offer valuable guidance to policymakers and financial institutions in formulating adaptive regulatory frameworks and promoting responsible financial innovation. Furthermore, this study underscores the importance of interdisciplinary collaboration in fostering fintech ecosystems. Mapping both achievements and research gaps provides a strategic roadmap for future academic inquiry and policy development, ultimately reinforcing fintech’s transformative impact on the financial sector.